Effect of task-oriented training on upper limb function in adults following stroke: a systematic review - Curtinha, Carolina (2019)
According to WHO, stroke is one of the three top causes of years of life lost due to premature mortality and is the leading cause of adult disability worldwide. Disability of the upper limb (UL) is one of the most common forms of impairment after stroke and functional limitations are the manifestation of the disability. Rehabilitation, such as physiotherapy, represents the major support of post-stroke health care. Task-oriented training (TOT), as part of the physiotherapy rehabilitation program, seems to be an efficient intervention for these patients. Purpose: To understand, through a review of the literature, the effect of TOT on UL functionality in adult individuals following stroke.